Standardization Comes to Virtualization. - Paulson, Linda Dailey (Computer (00189162), 2007)
The article provides information on virtualization software. Virtualization software enables a single computer to run multiple operating systems (OS) simultaneously, through the use of virtual machines (VM). This technology enables organizations to use a single server for multiple tasks that would usually have to run on multiple servers, each performing on a different OS. Because companies do not need to use as many servers they are able to save money. Also included are vendors like Microsoft, VMware, and XenSource, and server makers Dell, Hewlett-Packard, and IBM working together on the Open Virtual Machine Format (OVF) in order to make VM compatible across multiple platforms.